Intercontinental spread of pyrimethamine-resistant malaria. - Roper, C; Pearce, R; Nair, S; Sharp, B; Nosten, F; Anderson, T (2004)
Here we present molecular evidence demonstrating that malaria parasites bearing high-level pyrimethamine resistance originally arrived in Africa from southeast Asia. The resistance alleles carried by these migrants are now spreading across Africa at an alarming rate, signaling the end of affordable malaria treatment and presenting sub-Saharan Africa with a public health crisis.